2014
DOI: 10.1038/srep04013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genome-wide analysis reveals different classes of enigmatic old yellow enzyme in fungi

Abstract: In this study, we systematically identify Old Yellow Enzymes (OYEs) from a diverse range of economically important fungi representing different ecology and lifestyle. Using active site residues and sequence alignments, we present a classification for these proteins into three distinct classes including a novel class (Class III) and assign names to sequences. Our in-depth phylogenetic analysis suggests a complex history of lineage-specific expansion and contraction for the OYE gene family in fungi. Comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…However, the fungal OYEs originate from different families such as Saccharomycotina [61,62], and Pezizomycotina [63,64]. Fewer studies have been performed on OYEs originating from plants.…”
Section: Phylogenetic Classification Of Oyesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fungal OYEs originate from different families such as Saccharomycotina [61,62], and Pezizomycotina [63,64]. Fewer studies have been performed on OYEs originating from plants.…”
Section: Phylogenetic Classification Of Oyesmentioning
confidence: 99%
“…In 2016, Nizam and co-workers performed a comprehensive study of 424 putative OYEs from 60 fungal species and indicated a novel group among fungal OYEs [63]. However, none of these enzymes has been characterised thus far.…”
Section: Phylogenetic Classification Of Oyesmentioning
confidence: 99%
“…To account for these differences in sequence and the resulting structural features, the old yellow enzyme family can be further divided into five subclasses [15]. While enzyme members of the subclass I, also termed "classical" old yellow enzymes, and class II, introduced by Scrutton's group in 2010 and dubbed "thermophilic-like" [23], have been well explored [7,14], the recently described class III-V are less well investigated [15,24].…”
Section: Isolated In 1932 Bymentioning
confidence: 99%
“…A recent fungal OYE classification by Nizam and collaborators [10,12] clearly showed that this class of enzymes is divided in 3 distinct groups according to the structural peculiarity (e.g. core of the active site, accessory residues, loop regions): class I, class II and class III.…”
Section: Introductionmentioning
confidence: 98%
“…Among the organisms where these enzymes have been described, fungi have been shown to possess a different number of OYEs homologs in their genomes [10].…”
Section: Introductionmentioning
confidence: 99%